Influence of Social Media Engagements on Satisfaction, Attitude, and Academic Expression: Exploring Behavior Patterns among Pre-Service Teachers - Ballara, Noli B.; Laforteza, Jomar Von R. (An Overview of Literature, Language and Education Research Vol. 2, 2024)
This study focuses on the impact of social media use on pre-service teachers' satisfaction, attitude, and academic expression. Data were collected using a researcher-designed questionnaire and semi-structured interviews with 10 participants. A random sample of 264 participants, stratified by sex, year level, and social media use, revealed high usage rates for platforms like Facebook, Messenger, and TikTok. While average satisfaction levels were similar across genders, year levels displayed variations in attitudes towards social media engagement. Interestingly, no significant differences were found in how pre-service teachers utilized social media for academic purposes throughout their program. Individuals spending more time on social media reported higher satisfaction, and positive correlations emerged between all three variables – satisfaction, attitude, and academic expression. The thematic analysis also highlighted mixed feelings towards the pre-service teacher program, with many expressing the value of social media as a tool for communication, accessing resources, and staying motivated. The study recommends that integrating social media into pre-service teacher programs requires a unique approach, addressing concerns about information reliability and distractions while harnessing its potential to enhance educational environments.